2016
DOI: 10.5009/gnl15261
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 rs738409 Polymorphism Associated with Hepatic Steatosis and Advanced Fibrosis in Patients with Chronic Hepatitis C Virus: A Meta-Analysis

Abstract: Background/Aims: The recognition of a correlation between patatin-like phospholipase domain containing-protein 3 (PNPLA3) rs738409 (C>G) and the severity of liver steatosis or fibrosis in chronic hepatitis C (CHC) has not reached a consensus. This meta-analysis sought to investigate with accuracy the association between the PNPLA3 rs738409 (C>G) polymorphism and liver steatosis and advanced fibrosis in CHC patients. Methods: We performed a comprehensive literature search from the PubMed, Embase, Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
(40 reference statements)
2
32
0
1
Order By: Relevance
“…Previous studies showed that PNPLA3 variations, especially the rs738409 polymorphism, are associated with hepatic fibrosis and steatosis among CHC patients . PNPLA3 rs738409 SNP can cause hepatic inflammation and consequently lead to fibrosis pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that PNPLA3 variations, especially the rs738409 polymorphism, are associated with hepatic fibrosis and steatosis among CHC patients . PNPLA3 rs738409 SNP can cause hepatic inflammation and consequently lead to fibrosis pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…The PNPLA3 (patatin-like phospholipase domain containing 3, also known as adiponutrin) p.I148M polymorphism is commonly regarded to be the risk factor for both increased fat accumulation and fibrosis (5,6). The association with steatosis was demonstrated in several candidate studies, whereas the link between PNPLA3 and liver scarring was substantiated by meta-analyses in patients with chronic hepatitis C virus (HCV) infection (7) and in alcoholics (8). The data concerning the involvement of TM6SF2 (transmembrane 6 superfamily member 2) in liver injury are less definitive.…”
Section: Characteristics Of the Study Cohortmentioning
confidence: 96%
“…in a recent meta-analysis [36] (Table 1). Interestingly, the impact of the SNP seems to be lower compared to fatty liver diseases, as indicated by the lower odds-ratios (OR) observed in carriers of rs738409 [G] with histological damage phenotypes in this etiology.…”
Section: Key Pointmentioning
confidence: 99%